Prohemostatic Treatment in Cardiac Surgery - Levy, Jerrold H.; Sniecinski, Roman M. (Seminars in Thrombosis and Hemostasis, 2012)
Cardiac surgical patients represent a unique group of patients where coagulopathy occurs due to multiple causes besides simple hemorrhagic blood loss. Hemodilution, inflammation, and hemostatic activation while on cardiopulmonary bypass all contribute to this problem and provide targets for therapeutic intervention. Current pharmacological strategies to reduce the need for allogeneic transfusions include both preemptive agents to decrease the potential for bleeding as well as prohemostatic agents to promote the coagulation process. This article will discuss pharmacological agents including antifibrinolytics, protamine, desmopressin, fibrinogen, purified protein concentrates, recombinant factor VIIa, factor XIII, and topical agents used in cardiac surgery.
Keywords: antifibrinolytics; protamine; desmopressin; fibrinogen; purified protein concentrates; recombinant factor VIIa; factor XIII